Numerical Modelling of Front Contact Alignment for High Efficiency Cd1-xZnxTe and Cd1-xMgxTe Solar Cells for Tandem Devices. (18th July 2018) - Liyanage, Geethika K.; Phillips, Adam B.; Alfadhili, Fadhil K.; Heben, Michael J.
Abstract: Wide bandgap Cd1-x Znx Te (CZT) and Cd1-x Mgx Te (CMT) have drawn attention as top cells in tandem devices. These materials allow tuning of the band gap over a wide range by controlling the Zn or Mg concentration with little alteration to the base CdTe properties. Historically, CdS has been used as a heterojunction partner for CZT or CMT devices. However, these devices show a significant lower open circuit voltage (VOC ) than expected for wide bandgap absorbers. Recent modelling work suggests that poor band alignment between the CdS emitter and absorber results in a high concentration of holes at the interface, which increased recombination and limits the VOC . This recombination should be exacerbated for wider bandgap absorbers such as CZT and CMT. In this study, we use numerical simulations with SCAPS-1D software to investigate the band alignment in the front contacts for wider bandgap CdTe based absorbers. Results show that by replacing the CdS with a wide bandgap emitter layer, the VOC can be greatly improved, though under certain conditions, the fill factor remains sensitive to the location of the emitter conduction band. As a result, different transparent front contacts were also investigated to determine a device structure required to produce a high performance CZT or CMT top-cell for tandems devices.